Know Yourself, Achieve Your Dreams: Psychoeducational Training on Self-Concept and Future Planning for Adolescents - Tri Handayani, Fina; Nanda Pratama, Haichal; Irsyad Fadzly, Ahmad; Khusniyah, Mir'atul; Alifiah Putri, Intan; Qur'aniyah, Millatil; Nor Halizah, Siti; Mufidah, Wardatul (Society : Jurnal Pengabdian Masyarakat, 2025)
During adolescence, the development of personal identity and self-image is crucial. In this phase, adolescents are searching for their identity, their vision of the future, and what they want. The "Know Yourself, Achieve Your Dreams" program was established as a training to help adolescents in forming a positive self-concept and fostering three important elements of self-perception: ideal self, self-image, and self-esteem. This initiative seeks to reduce the gap between the perfect self and the real self by exploring hobbies, reflecting on personal beliefs, and setting achievable life goals. The technique used is psychoeducational self-concept training. Training tasks include learning reflection, showing inspirational videos, writing letters to yourself in the future, and group discussions. This program has been shown to be important in helping adolescents' social and emotional growth and can act as a preventive measure against poor self-concept and identity confusion.